Perianal Crohn’s Disease is associated with distal colonic disease, stricturing disease behavior, IBD-associated serologies and genetic variation in the JAK-STAT pathway - Kaur, Manreet (Inflamm Bowel Dis, 2016)
BACKGROUND: Perianal Crohn’s Disease (pCD) is a particularly severe phenotype associated with poor quality of life with a reported prevalence of 12%–40%. Previous studies investigating the etiology of pCD have been limited in the numbers of subjects and the intensity of genotyping. The aim of this study was to identify clinical, serological and genetic factors associated with pCD. METHODS: We performed a case-control study comparing patients with (pCD+) and without perianal (pCD−) involvement in CD; defined as the presence of perianal abscesses or fistulae. Data on demographics and clinical features were obtained by chart review. IBD related serology were determined by ELISA. Genetic data were generated using Illumina genotyping platforms RESULTS: We included 1721 patients with CD of which 524 (30.4%) were pCD+ and 1197 were pPCD−. Perianal CD was associated with distal colonic disease (OR 5.54 [3.23–9.52], p < 0.001), stricturing disease behavior (1.44 [1.14–1.81], p= 0.002) and family history of inflammatory bowel disease (4.98 [3.30–7.46], p < 0.001). Perianal CD was associated with higher ASCA IgA (p <0.001) and OmpC (p= 0.008) antibody levels. Perianal CD was associated with known IBD loci including KIF3B; CRTC3; TRAF3IP2; JAZF1; NRIP1; MST1; FUT2; and PTGER (all p<0.05). We also identified genetic association with genes involved in autophagy (DAPK1, p=5.11×10(−5)); TNF alpha pathways (NUCB2, p=8.68×10(−5); DAPK1); IFNg pathways (DAPK1; NDFIP2, p=8.74×10(−5)) and extracellular matrix and scaffolding proteins (USH1C, p=8.68×10(−5); NDFIP2; TMC07, p=8.87×10(−5)). Pathway analyses implicated the JAK/Stat pathway (p(c) = 3.72 × 10(−5)). CONCLUSION: We have identified associations between perianal Crohn’s disease, more distal colonic inflammation, Crohn’s disease-associated serologies, and genetic variation in the JAK/Stat pathway